Kepemimpinan Hulu Apad Tinggan Ditinjau dari Sistem Pemerintana Demokrasi di Indodesia - I Wayan Suarjaya (UHN IGB Sugriwa Denpasar, 2016)
The Hulu Apad is a sporadic traditional Balinese organisation that is developing mainly in highland areas of the island. This writing studies the traditional Pakraman system of the organisation when seen from the Indonesian governmental democratic point of view, namely the process of deciding the system, the main task, and the function of every representation of the organisation at a village.